Un modello basato sulla teoria dei grafi per l’individuazione di isomorfismi distrettuali geograficamente non prossimi. Il caso dei distretti industriali italiani - Stefano De Falco (Bollettino della Società Geografica Italiana)
A dichotomy often frequent in the context of geographic studies concerns the dualism between propagation and induction models-based phenomena, inherent in variables and factors characterizing contiguous areas, and research relating to homogeneity between geographically not closed areas. In the wake of the latter research, this contribution proposes a model that exploits the potential of graph theory for the evaluation of common dynamics relating to non-contiguous areas. The assumption underlying the model envisages configuring the reality being studied in terms of a network whose nodes and branches are respectively representative of entities distant from each other and of their related affinities. The proposed approach focuses on some Italian industrial districts. The value of the proposed approach is twofold, on the one hand regarding the specific industrial district topic with both scientific and practical implications, and on the other hand it aims to provide a method that can be replicated in similar scenarios in which it is interesting to evaluate the similarity between neighboring areas analytically.